2004
DOI: 10.4049/jimmunol.172.2.1132
|View full text |Cite
|
Sign up to set email alerts
|

T Cytotoxic-1 CD8+ T Cells Are Effector Cells against Pneumocystis in Mice

Abstract: Host defenses are profoundly compromised in HIV-infected hosts due to progressive depletion of CD4+ T lymphocytes. A hallmark of HIV infection is Pneumocystis carinii (PC) pneumonia. Recently, CD8+ T cells, which are recruited to the lung in large numbers in response to PC infection, have been associated with some level of host defense as well as contributing to lung injury in BALB/c mice. In this study, we show that CD8+ T cells that have a T cytotoxic-1 response to PC in BALB/c mice, as determined by secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 39 publications
(42 reference statements)
3
43
1
Order By: Relevance
“…It is also apparent that CD4 ϩ CD25 ϩ FoxP3 ϩ T cells are not effector cells against Pneumocystis. The role of CD8 T cells in organism clearance and lung injury associated with PCP is a complex issue with contradicting reports (13,35,36,38). Although further study is necessary to clearly define CD8 ϩ T cell responses, our data suggest there is a delayed injury response mediated by these cells as opposed to CD4 ϩ CD25 Ϫ T cells.…”
Section: Cd4contrasting
confidence: 37%
See 2 more Smart Citations
“…It is also apparent that CD4 ϩ CD25 ϩ FoxP3 ϩ T cells are not effector cells against Pneumocystis. The role of CD8 T cells in organism clearance and lung injury associated with PCP is a complex issue with contradicting reports (13,35,36,38). Although further study is necessary to clearly define CD8 ϩ T cell responses, our data suggest there is a delayed injury response mediated by these cells as opposed to CD4 ϩ CD25 Ϫ T cells.…”
Section: Cd4contrasting
confidence: 37%
“…Previous studies from our laboratory have shown that reconstitution of Pneumocystis-infected SCID mice with nonpolarized CD8 ϩ cells is not sufficient to promote organism clearance (36). Although IFN-␥ levels in the lungs of animals reconstituted with CD4…”
Section: Cd4mentioning
confidence: 92%
See 1 more Smart Citation
“…ϩ -T-cell-depleted mice from development of PCP (10,11,14). However, these interesting studies of the effect of gamma interferon addressed a different issue about the biology of CD8…”
Section: Discussionmentioning
confidence: 99%
“…In the gamma interferon studies the workers used mice that were challenged with P. carinii 24 h after transfection of lung cells with a gamma interferon gene (10,14) or 24 h before infusion of CD8 ϩ T cells isolated from mice that had been transfected with the gamma interferon gene (11). In these studies, gamma interferon-stimulated CD8 ϩ T cells protected against the development of PCP rather than controlled an established infection.…”
Section: Discussionmentioning
confidence: 99%